Predictors of neurosurgical intervention in complicated mild traumatic brain injury patients: a retrospective cohort study. (24th August 2021) - Tourigny, Jean-Nicolas; Paquet, Véronique; Fortier, Émile; Malo, Christian; Mercier, Éric; Chauny, Jean-Marc; Clark, Gregory; Blanchard, Pierre-Gilles; Boucher, Valérie; Carmichael, Pierre-Hugues; Gariépy, Jean-Luc; Émond, Marcel
ABSTRACT: Objectives: To determine the predicting demographic, clinical and radiological factors for neurosurgical intervention in complicated mild traumatic brain injury (mTBI) patients. Methods: Design: retrospective multicenter cohort study. Participants: patients aged ≥16 presenting to all level-I trauma centers in Quebec between 09/2016 and 12/2017 with mTBI(GCS 13–15) and complication on initial head CT (intracranial hemorrhage/skull fracture). Procedure: Consecutive medical records were reviewed and separated into two groups: no neurosurgical intervention and neurosurgical intervention (NSI). Main outcome: neurosurgical intervention. Analysis: multiple logistic regression model. Results: Four hundred and seventy-eight patients were included and 40 underwent NSI. One patient had radiological deterioration but no clinical deterioration prior to surgery. Subdural hemorrhage ≥4 mm width (OR:3.755 [95% CI:1.290–10.928]) and midline shift (OR:7.507 [95% CI: 3.317–16.989]) increased the risk of NSI. Subarachnoid hemorrhage was associated with a lower risk of NSI (OR:0.312 [95% CI: 0.136–0.713]). All other intracranial hemorrhages were not associated with NSI. Conclusion: Radiological deterioration was not associated with the incidence of NSI. Subdural hemorrhage and midline shift should be predicting factors for neurosurgery. Some patients with isolated findings such as subarachnoid hemorrhage could be safely managed in their original center without being transferred to a level-I trauma center.